Waterborne Polyurethane Polymer Electrolytes Containing Poly(ethylene glycol) and Polydimethylsiloxane in Soft Segments - Li, Yue-Jiao; Chen, Shi; Wu, Feng (Asian Journal of Chemistry, 2014)
New waterborne polyurethane polymer electrolytes containing poly(ethylene glycol) and polydimethylsiloxane (PDMS) in the soft segments were designed and synthesized. The structure and performance of the electrolytes were characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, thermogravimetric analysis, electrochemical impedance spectroscopy and linear sweep voltammetry. The membranes exhibited good electrochemical stability. The thermal stability of the polymer electrolytes increased with increased content of polydimethylsiloxane. The conductivity results indicated that the incorporation of polydimethylsiloxane up to a certain amount (17 wt %) increased the ionic conductivity, but further addition decreased the conductivity. Gel polymer electrolytes were obtained by immersing polymer membranes in 1 M LiTFSI/DMC+EC (DMC:EC = 1:1 by weight) for different durations. These electrolytes possessed good ionic conductivity, i.e., ca. 2.52 × 10-3 S/cm with a swollen percentage of 130 wt % at room temperature.